Gene body DNA hydroxymethylation restricts the magnitude of transcriptional changes during aging - Occean, James R.; Yang, Na; Sun, Yan; Dawkins, Marshall S.; Munk, Rachel; Belair, Cedric; Dar, Showkat; Anerillas, Carlos; Wang, Lin; Shi, Changyou; Dunn, Christopher; Bernier, Michel; et al. (Nature communications, 2024)
DNA hydroxymethylation (5hmC), the most abundant oxidative derivative of DNA methylation, is typically enriched at enhancers and gene bodies of transcriptionally active and tissue-specific genes. Although aberrant genomic 5hmC has been implicated in age-related diseases, its functional role in aging remains unknown. Here, using mouse liver and cerebellum as model organs, we show that 5hmC accumulates in gene bodies associated with tissue-specific function and restricts the magnitude of gene expression changes with age. Mechanistically, 5hmC decreases the binding of splicing associated factors and correlates with age-related alternative splicing events. We found that various age-related contexts, such as prolonged quiescence and senescence, drive the accumulation of 5hmC with age. We provide evidence that this age-related transcriptionally restrictive function is conserved in mouse and human tissues. Our findings reveal that 5hmC regulates tissue-specific function and may play a role in longevity. DNA hydroxymethylation (5hmC) is typically altered in age-related diseases. Here, the authors show that 5hmC accumulates in gene bodies, partially due to prolonged quiescence, and restricts the magnitude of transcriptional changes with age.